2011
DOI: 10.4314/ijmu.v6i2.68186
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of obesity and hypertension among adults in Ogbomoso, Nigeria

Abstract: Developing countries are now witnessing an increase in overweight; obesity and obesity-related morbidity. We determined the prevalence of obesity using the measure of body mass index (BMI) and hypertension and the association between obesity and hypertension among adults in Ogbomoso, Nigeria. A cross-sectional descriptive study of 400 adults was carried out. Participants were administered a standardized questionnaire and had measurements of weight, height and blood pressure taken. Four hundred subjects were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 12 publications
4
14
2
Order By: Relevance
“…The obesity prevalence of 17.2% is lower than the 19.2 % and 22.6% observed by Ulasi et al in a semi-urban community and among market workers respectively 12 . However, the data showed that BMI is a positive predictor of high BP, OR 1.08, (CI 1.03, 1.13. p=0.001), which is similar to the finding from several other studies 12,16,17,25,26 .…”
Section: Predictors Of High Bpsupporting
confidence: 91%
See 1 more Smart Citation
“…The obesity prevalence of 17.2% is lower than the 19.2 % and 22.6% observed by Ulasi et al in a semi-urban community and among market workers respectively 12 . However, the data showed that BMI is a positive predictor of high BP, OR 1.08, (CI 1.03, 1.13. p=0.001), which is similar to the finding from several other studies 12,16,17,25,26 .…”
Section: Predictors Of High Bpsupporting
confidence: 91%
“…Several other studies have recorded lower prevalence rates of high BP in Nigeria, [16][17][18][19][20][21][22] other West African countries 23,24 and even East Africa 25 . However, in a facility based study in south west Nigeria, 50.5% of the adults who attended the health facility were found to have high BP 26 , also economically developed countries have documented prevalence as high as 50% 27 , and 49.4% of residents in a rural community in Spain had high BP 25 . The high prevalence of high BP noticed in this study is a reflection of the increasing prevalence of hypertension that is occurring in all regions of the world.…”
Section: Prevalence Of High Bpmentioning
confidence: 93%
“…Perez-Cueto et al [26] in a study among 15-19 year old Jamaicans revealed that high waist circumference was 10% and this results is similar to the findings of this study. Amole et al [9] also showed that the prevalence of high waist circumference was 33.8% among adults in Ogbomosho.…”
Section: Discussionmentioning
confidence: 99%
“…when caloric intake exceeds energy expenditure [3], [4]. This leads to excessive accumulation of fat in the adipose tissue of the body and this is associated with and predisposes to the development of Non Communicable Diseases (CVD) such as Type 2 diabetes, coronary heart disease, atherosclerosis, hypercholesterolemia, stroke, hypertension, different types of cancers, asthma, other respiratory diseases, increased morbidity and mortality [2]- [3], [5]- [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation